2016
DOI: 10.18632/oncotarget.9729
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and use of HapT1-derived homologous tumors as a preclinical model to evaluate therapeutic efficacy of drugs against pancreatic tumor desmoplasia

Abstract: Desmoplasia in human pancreatic cancer (PC) promotes cancer progression and hinders effective drug delivery. The objectives of this study were to characterize a homologous orthotopic model of PC in Syrian golden hamster and investigate the effect of anti-fibrotic (pirfenidone), antioxidant (N-acetyl cysteine, NAC) and anti-addiction (disulfiram, DSF) drugs on desmoplasia and tumor growth in this model. The HapT1 PC cells when implanted orthotopically into hamsters formed tumors with morphological, cellular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…Then cells were harvested in RLT buffer and processed for RNA isolation as described by the manufacturer (Qiagen, USA). RNA quantification was carried out using Nanodrop followed by cDNA synthesis [10]. The expression levels of Il-1, Tnf-, Vegf, and Il-6 were analyzed in all the cDNA samples through qPCR, by using gene-specific primers.…”
Section: Effect Of Mif On the Expression Of Inflammation-associated Gmentioning
confidence: 99%
See 3 more Smart Citations
“…Then cells were harvested in RLT buffer and processed for RNA isolation as described by the manufacturer (Qiagen, USA). RNA quantification was carried out using Nanodrop followed by cDNA synthesis [10]. The expression levels of Il-1, Tnf-, Vegf, and Il-6 were analyzed in all the cDNA samples through qPCR, by using gene-specific primers.…”
Section: Effect Of Mif On the Expression Of Inflammation-associated Gmentioning
confidence: 99%
“…Hamsters are important animal models for studying various infectious diseases of humans [1][2][3][4][5][6][7][8]. The hamster models of pancreatic and oral cancer have gained importance in their respective fields [9][10][11][12][13][14]. Moreover, these animals have also been instrumental in studying metabolic and/or inflammatory diseases like diabetes and pancreatitis [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment with pirfenidone inhibited PSC growth, migration, invasion, and ECM production. In preclinical studies pirfenidone has demonstrated some promising effects in combination with gemcitabine, with β‐cyclodextrin MMP2 responsive liposome and with the antioxidant N ‐acetyl cysteine . This compound has yet to be evaluated in human trials.…”
Section: Introduction: Pancreas Cancermentioning
confidence: 99%